Dentinal Hypersensitivity Treatment Using Diode Laser 980 nm: In Vivo Study - Marwan El Mobadder; Amaury Namour; Mélanie Namour; Walid Dib; Wassim El Mobadder; Elie Maalouf; Sabine Geerts; Toni Zeinoun; Samir Nammour (MDPI AG, 2019)
The discomfort of patients due to dentinal hypersensitivity (DH) is one of the main challenges that dentists face in daily practice. Difficulties in DH treatment gave rise to many protocols which are currently used. The aim of this clinical study is to evaluate the effectiveness of a new protocol on the reduction of dentinal hypersensitivity with diode laser 980 nm and the application of a graphite paste. 184 patients enrolled in the study, the degree of pain was evaluated by visual analog scale (VAS), graphite paste was applied on the exposed dentine before irradiation, the application of diode laser 980 nm with continuous mode, backward motion, tangential incidence of the beam in non-contact mode and a delivery output of 1 W. Fiber’s diameter was 320 μm and total exposure time depended on the time necessary to remove the graphite paste from the teeth. Statistical analyses were performed with Prism 5® software. Pain in post-operative significantly decreased immediately after the treatment. Mean values stayed stable until a 6-month follow-up. The application is considered to be safe with long-term effectiveness.